Alumni and Stakeholder Satisfaction Toward Political Science Department of UNTL - Costa, Por Henrique Cesário da; Martin, Martinho; Santos, Abrão dos; Esteves, Saturlino; Freitas, Franquelino (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The evaluation of higher education quality requires active participation from all stakeholders, particularly alumni and employers. This research investigates the degree of satisfaction and feedback from alumni and stakeholders in five municipalities (Aileu, Baucau, Ermera, Manatuto, and Liquiça) regarding the Political Science Department of the Faculty of Social Sciences and Politics (FCSP) at the National University Timor Lorosa'e (UNTL). Using a qualitative and descriptive approach with semi-structured interviews, the study collected perceptions from 27 alumni and 21 employers about course relevance, training quality, and labor market applicability. Results indicate that 93% of alumni worked in the public sector, with 93% reporting that their training significantly contributed to professional performance. Alumni satisfaction was high, with 81% very satisfied and 15% satisfied with the course. Employers confirmed that Political Science graduates demonstrated strong adaptation abilities and rule compliance in the workplace. The study recommends infrastructure improvements, continuing education programs, and enhanced training in political science and citizenship to maintain the department's relevance in developing future leaders for Timor-Leste.